Inorganic solid wastes from agrosilvopastoral sector in Ceres, Goiás, Brazil - Sousa, Ana Paula Veloso de Assis; Rosseto, Renato; Zaneti, Izabel Cristina Bruno Bacellar; Peixoto, Josana de Castro; Rosseto, Lucimar Pinheiro (Sustainability in Debate, 2019)
This study aimed to verify the application of available legislation about to the production, quantity and appropriate disposal of inorganic solid wastes from agrosilvopastoral activities in Ceres/GO. The research had a descriptive character, with bibliographic, documentary and field research methods, based on quali-quantitative approaches, and the gathering of primary and secondary data. The data were extracted from official records and websites, including information of public and private institutions, and sourced by professional entities and associations responsible for collection, sorting, recycling and final disposal of solid wastes. On the basis of the obtained information, although Ceres/GO city has a small rural population, it was considered as good study model. The efforts and experiences carried out in Brazil and different countries gives us insights to understand and propose solutions related to the waste management from agrosilvopastoral system in Ceres/GO, which may be expanded into other Brazilian cities.